The 8th International Conference on Robotic, Vision, Signal Processing & Power Applications Innovation Excellence Towards Humanistic Technology - Mat Sakim, Harsa Amylia; Mustaffa, Mohd Tafir (Lecture Notes in Electrical Engineering,, 2014)
The proceeding is a collection of research papers presented, at the 8th International Conference on Robotics, Vision, Signal Processing and Power Applications (ROVISP 2013), by researchers, scientists, engineers, academicians as well as industrial professionals from all around the globe. The topics of interest are as follows but are not limited to: â_¢ Robotics, Control, Mechatronics and Automation â_¢ Vision, Image, and Signal Processing â_¢ Artificial Intelligence and Computer Applications â_¢ Electronic Design and Applications â_¢ Telecommunication Systems and Applications â_¢ Power System and Industrial Applications Â .